Pemilihan Pemasok Bahan Mentah pada Restoran Menggunakan Metode Fuzzy Analytical Hierarchy Process - Elta Sonalitha; M. Sarosa; Agus Naba (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2015)
Production in the restaurant is a continuous production that must be provided with uncertain request based on the consumer demand. Availability of raw materials is preferred to support the production process. In purchasing management it is often difficult to choose the right supplier of raw materials for each process order. The purpose of this research is to implement the method of Fuzzy Analytical Hierarchy Process (FAHP) in the Decision Support System (DSS) purchase of raw materials to suppliers. The addition of fuzzy logic in AHP is used to enhance the accuracy of subjectivity in the process of purchasing management assessment for each criteria and alternatives.